Keterbacaan Buku Teks Keterbacaan Buku Teks Bahasa Sunda Rancagé Diajar Kelas X Untuk SMA/SMK/MAK (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
Determining textbooks in legibility relates to a sentence or text form which when read is easy to understand, understand and remember the intent and meaning of the text. Readability is all elements of reading that affect the success achieved by a group of readers with the material. In Sundanese language textbooks at the SMA/SMK/MA/MAK level and equivalent. The level of readability of the discourse will affect students' understanding of the content (material) presented in a book. The purpose of this research is to determine whether the textbook can be read or used effectively by students. The method used in this research is descriptive qualitative by using literature study technique. The source of the research data is a Sundanese language textbook entitled Rancage Diajar Pikeun SMA/SMK/MA/MAK students grade X curriculum 2013 revision 2017. After being analyzed, the textbook has criteria that are very feasible and easy to understand.